Aplikasi Doa Dan Surah Pendek Berbasis Andriod Sebagai Media Pembelajaran Untuk Anak Usia Dini - M Ghufroni An'ars; Parjito Parjito; Hendar Juliyanto (CV. Keranjang Teknologi Media, 2023)
The problem in this study is the lack of educators in the field of Islam and inadequate learning media hamper the learning process of prayer and short surahs. Harapan Bunda Integrated Islamic Conservation Kindergarten faces similar problems in its location. Therefore, the development of Android applications as an interesting and effective learning medium is needed to improve the learning outcomes of learners in memorizing prayers and short surahs. Extreme Programming (XP) methods are used in the development of this application with four stages: planning, design, coding, and testing. The planning stage analyzes the needs of the system and the problems encountered. The design phase designs models and interfaces using Figma. The coding phase uses Java and Android Studio as the IDE for the Android operating system. The testing phase tests the feasibility of the system using ISO 9126, focusing on fuctionality and usability. The result of this study is an Android application as a medium for learning prayers and short surahs. The test involved 23 respondents with percentage results of 100% for the functionality aspect and 98.43% for the usability aspect. This shows that educators and students strongly agree with the application and the application can be used in learning.